Implementasi Pembelajaran Model Problem Based Learning pada Mata Pelajaran Sejarah Indonesia Kelas 10 MA Bustanul Muta’allimin Blitar - Henda Armanda (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
This study aims to describe the learning conditions of Indonesian History applied at Madrasah Aliyah Bustanul Muta'allimim Blitar which uses the Problem Based Learning learning model. Problem Based Learning model learning directs the ability of students to play an active role in solving a problem in the process of learning activities, but in reality in learning in class 10 of Madrasah Aliyah Bustanul Muta'allimin there are still some students who still have difficulty in solving problems and there are also some students who are less active when the learning process takes place. The formulation of the problems in this study are: 1) How is the implementation of the Problem Based Learning learning model in grade 10 Indonesian History subjects? 2) How can the implementation of Problem Based Learning improve the quality of 10th grade Indonesian History learning? 3) What are the implications of the implementation of Problem Based Learning on student learning outcomes? The method used in this research is descriptive qualitative, as for the data sources used, namely through primary data by digging directly to the research location located at MA Bustanul Muta'allimin Blitar, with data collection techniques using interviews, observation, and documentation and checking data validity through source triangulation. . The results of this study are 1) Implementation of Problem Based Learning model learning in Indonesian History subjects in class 10 A, 10 B and 10 C there are three stages that are applied in the learning process, namely the preparation stage, the core activity stage, and the final stage or evaluation. 2) Analysis of Whether the Problem Based Learning Method can Improve the Quality of Indonesian History Learning in grade 10. There are differences in the responses of students from the three classes for class 10 A, the response of students is still difficult in solving problems in the learning process and difficulty in presenting material when in front of the class and less active in learning in class, this is different from class 10 B and 10 C, students are easier in solving a problem and can present material and be active in learning activities in class. So from this it can be said that learning in the classroom has improved, but there must be more improvements from the Problem Based Learning model when learning activities take place in class. 3) Classroom student learning outcomes For student learning outcomes are influenced by factors within students, namely about the motivation of these students in participating in learning. Students from the three classes can be said to be class 10 A which is rather low compared to the other classes, because there are only male students, this can happen because in the application of Problem Based Learning model learning, these students do not pay attention to the teacher's direction, and are less serious in learning activities, so they do not understand the material being discussed together, in contrast to classes 10 B and 10 C which tend to be more easily organized by the teacher and pay attention when learning activities take place and are active in the process of ongoing learning activities.